A guide to children's Bible story books in twentieth century America: to hold and to have - Magness, Patricia Phillips (Lang, 2001)
Twentieth-century America has produced an abundance of richly illustrated children's Bible storybooks, many of high literary and artistic quality. This guide selects and analyzes 134 of these books that both meet high critical standards and show respect for their Old and New Testament source as a traditional literary universe of sacred numina. Here presented individually with extended, number-coded annotations, these storybooks are argued to have a figurative profundity inseparable from their appeal to children. They are categorized into three basic types and indexed by author, illustrator, title, subject, and level of difficulty.